Agricultural development and its impact on malaria: Azerbaijan - Temel, Tugrul; Ejov, Michael (International Service for National Agricultural Research, 2001)
This paper discusses the malaria situation in Azerbaijan during the period 1991-2000, drawing lessons from the past and suggesting measures to avoid future epidemics. Statistical methods are applied and geographical maps produced to determine the key agricultural and environmental determinants of malaria. Results strongly suggest that the fight against malaria should give priority to the effective use of irrigation water, to the reduction of land salinization, and to the rehabilitation of rural road networks. This fight should involve the agricultural, environmental, and health sectors, and critical gaps should be identified in understanding of where joined forces can make a difference in livelihood of the infected population. Such a multi-sectoral framework should help prevent the future threats due to changing crop pattern, rising water levels in the Caspian Sea, and sleeping parasites in the communities already hit worse.